2021
DOI: 10.2147/ott.s291823
|View full text |Cite
|
Sign up to set email alerts
|

CircHIPK2 Contributes to DDP Resistance and Malignant Behaviors of DDP-Resistant Ovarian Cancer Cells Both in vitro and in vivo Through circHIPK2/miR-338-3p/CHTOP ceRNA Pathway

Abstract: Background: Cisplatin (DDP) is standard-of-care and first-line management for ovarian cancer (OvCa). Circular RNA HIPK2 (circHIPK2) is abnormally upregulated in serum of OvCa patients. However, its role in DDP resistance remains unclear. Methods: Expression of cirHIPK2, microRNA (miR)-338-3p and chromatin target of protein arginine methyltransferase (CHTOP) was detected by quantitative reverse transcription PCR and Western blotting. Functional experiments were performed using cell counting kit-8 assay, flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Chemotherapy drugs like cisplatin and other platinum agents have wide application in solid tumors, such as LUAD, as main anticancer agents. Nevertheless, efficacy decreased due to the emergence of drug resistance (Cao et al, 2021;He et al, 2022). More and more studies add up to the statement that miRNAs feature in cancer development and drug resistance (Hussen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy drugs like cisplatin and other platinum agents have wide application in solid tumors, such as LUAD, as main anticancer agents. Nevertheless, efficacy decreased due to the emergence of drug resistance (Cao et al, 2021;He et al, 2022). More and more studies add up to the statement that miRNAs feature in cancer development and drug resistance (Hussen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For the ceRNA mechanism, multiple circRNAs have been proved to interacting with miRNA and protein‐coding RNA in human cancers. For example, suppression of CirchipK2 was reported to inhibit the DDP resistance in ovarian cancer (OVC) through regulating CHTOP as a ceRNA approach 24 . In addition, circ_0032822 could promote the prognosis of laryngeal cancer through the miR‐141/E2F3 axis 25 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, suppression of CirchipK2 was reported to inhibit the DDP resistance in ovarian cancer (OVC) through regulating CHTOP as a ceRNA approach. 24 In addition, circ_0032822 could promote the prognosis of laryngeal cancer through the miR‐141/E2F3 axis. 25 Previously, research also showed that increased miR‐190a could suppress the expression of PAR1 and induced the inhibition of cell migration and invasion in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The coincidence targets in these different pathways provide some support for us to analyze the generation of drug resistance of tumor cells as a whole. For example, miR-338-3p can play a role in promoting drug resistance in a variety of tumors according to current reports ( 99 , 106 ), but the mechanisms of action are different. It is worth thinking whether the regulatory mechanisms of the same miRNAs in different tumor lines overlap, and if not, what determines the target of miRNAs to exert regulatory effects in tumor cells, and if so, whether it is of limited significance to focus on individual pathways according to most of the current literature.…”
Section: Circrnas Alter the Copy Number Of Target Genes And Activate ...mentioning
confidence: 98%
“…For example, also in non-small cell lung cancer, circRNAPRMT5 can target miR-381-3p ( 24 ) and miR-4458 ( 26 ) to regulate the expression of different downstream proteins to promote tumor, and the same circ_007630 can also target miR-296-5p ( 31 ) and miR-186-5p ( 51 ) respectively. Interestingly, the same miRNA targets different genes in different tumors and regulates downstream pathways, such as miR-338-3p, which promotes the progressive drug resistance of oral squamous cell carcinoma ( 99 ) and ovarian cancer ( 106 ) at the same time. As we all know, the effect of circRNA on tumor drug resistance is often the result of a variety of mechanisms, so we need to pay attention to the interaction between various mechanisms and pathways, and pay attention to the integration and analysis of various mechanism information.…”
Section: Circrnas Alter the Copy Number Of Target Genes And Activate ...mentioning
confidence: 99%